O gênero conto nos anos finais do ensino fundamental: leitura e produção de texto - SANCHES, Murilo Henrique da Cruz (2023)
This work presents as its theme The short story genre in the final years of elementary school: reading and text production. The general objective of the study is to analyze the short story genre as a learning strategy in the development of reading skills and text production and specific objectives: Identify the characteristics of the short story genre; understand the importance of the short story genre for the processes of reading and textual production; to develop a didactic intervention proposal for the development of reading skills and text production, with 9th grade students. year through the short story genre. The theoretical-methodological framework is based on the vision of didactic sequence according to Dolz, Noverraz and Schneuwly (2004) and Zabala (1998); in the discourse genres in the view of Bakhtin (1997) and Antunes (2002); in the short story genre based on Costa (2014) and Gotlib (1990); in works on textual typologies by Marcuschi (2008) and in guidelines of the National Common Curricular Base BNCC (2018), which brings proposals for language teaching based on the study of genres. Subsequently, after applying the SD, the second part of the work, it will be proven that the student has achieved knowledge of the structure, characteristics and social function of the short story genre; understood the relevance of this genre as a stimulus to reading and writing; and was able to competently produce a short story.